2021
DOI: 10.1111/sms.13930
|View full text |Cite
|
Sign up to set email alerts
|

Does exercise intensity matter for fatigue during (neo‐)adjuvant cancer treatment? The Phys‐Can randomized clinical trial

Abstract: Exercise during cancer treatment improves cancer‐related fatigue (CRF), but the importance of exercise intensity for CRF is unclear. We compared the effects of high‐ vs low‐to‐moderate‐intensity exercise with or without additional behavior change support (BCS) on CRF in patients undergoing (neo‐)adjuvant cancer treatment. This was a multicenter, 2x2 factorial design randomized controlled trial (Clinical Trials NCT02473003) in Sweden. Participants recently diagnosed with breast (n = 457), prostate (n = 97) or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(96 citation statements)
references
References 45 publications
4
90
0
2
Order By: Relevance
“…One study with an acceptance rate below 30% [15] identi ed three main reasons for declining participation; 1) lack of interest in the study, 2) felt too busy to participate and 3) did not want to travel to the training facility. These results are in line with the ndings in the Phys-Can RCT, where travel distance was the major reason for declining participation [9]. Although not stated as a reason in the present study, it is possible that the randomization to two different exercise intensities may have deterred eligible participants as they may have been hesitant to exercise at a non-preferred intensity.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…One study with an acceptance rate below 30% [15] identi ed three main reasons for declining participation; 1) lack of interest in the study, 2) felt too busy to participate and 3) did not want to travel to the training facility. These results are in line with the ndings in the Phys-Can RCT, where travel distance was the major reason for declining participation [9]. Although not stated as a reason in the present study, it is possible that the randomization to two different exercise intensities may have deterred eligible participants as they may have been hesitant to exercise at a non-preferred intensity.…”
Section: Discussionsupporting
confidence: 89%
“…The Phys-Can randomized controlled trial This study used data from the Physical Training and Cancer (Phys-Can) intervention study [3,9]. The primary aim of the Phys-Can RCT was to compare the effects of low-to-moderate (LMI) vs high-intensity (HI) exercise, with or without additional behavior change support (goal-setting, self-monitoring, action planning, review of goal-setting and problem solving), on cancer-related fatigue in patients undergoing cancer treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, higher exercise intensities appear to protect against chemotherapy-related inflammation [ 81 ], a mechanism involved in the pathogenesis of fatigue [ 82 ], which could be clinically relevant for patients eligible to adjuvant treatment after surgery. This rationale is supported by a large clinical trial which found that a combination of high-intensity aerobic and resistance exercise was significantly more effective to reduce physical fatigue compared to low-to-moderate-intensity exercise in cancer patients undergoing (neo-)adjuvant treatment [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moderate-to-vigorous intensity physical activity was assessed using SenseWear Armband mini (BodyMedia Inc, Pittsburgh, PA, USA) as previously described [9]. Mean time (minutes) in moderate-to-vigorous intensity physical activity (MVPV) per 24 h was considered that of at least 3 METs according to SenseWear algorithms [11].…”
Section: Completers N=410mentioning
confidence: 99%